Chemical composition, antioxidant, antimicrobial and antiproliferative activities of the extracts isolated from the pomace of rowanberry (Sorbus aucuparia L.). (October 2020) - Bobinaitė, Ramunė; Grootaert, Charlotte; Van Camp, John; Šarkinas, Antanas; Liaudanskas, Mindaugas; Žvikas, Vaidotas; Viškelis, Pranas; Rimantas Venskutonis, Petras
Graphical abstract: Highlights: Rowanberry pomace was fractionated by increasing polarity pressurized solvents. Neochlorogenic and chlorogenic acids were the main compounds in the extracts. The extracts effectively inhibited the growth of some tested microorganisms. Acetone and water extracts showed higher cytotoxic potential in cell assays. Rowanberry pomace is a promising source of natural bioactive antioxidants. Abstract: In the present work, acetone, ethanol and water extracts of rowanberry ( Sorbus aucuparia L.) pomace were evaluated for their antiproliferative, antimicrobial and antioxidative effects. Chemical composition of the extracts was determined by UPLC-ESI-MS/MS and spectrophotometric methods. Neochlorogenic and chlorogenic acids were the major phenolic compounds. The water extract contained the highest total proanthocyanidins content (301 ± 18.9 mg/g) and demonstrated the highest antioxidant activity in the all assays (DPPH, FRAP and ORAC). Extracts isolated from rowanberry pomace effectively inhibited the growth of undesirable microorganisms, especially Gram-positive bacteria. Acetone extract was the strongest antimicrobial agent followed by water and ethanol extracts. Acetone and water extracts demonstrated also higher cytotoxic potential in cell viability assays (SRB and MTT) using Caco-2 cells. In general, the results suggest that rowanberry pomace is a promising source of natural compounds with antioxidant and biological activities.